2009
DOI: 10.1172/jci36806
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin1 mediates nicotinic acid–induced flushing, but not its antilipolytic effect, in mice

Abstract: Nicotinic acid is one of the most effective agents for both lowering triglycerides and raising HDL. However, the side effect of cutaneous flushing severely limits patient compliance. As nicotinic acid stimulates the GPCR GPR109A and G i /G o proteins, here we dissected the roles of G proteins and the adaptor proteins, β-arrestins, in nicotinic acid-induced signaling and physiological responses. In a human cell line-based signaling assay, nicotinic acid stimulation led to pertussis toxin-sensitive lowering of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
174
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(190 citation statements)
references
References 48 publications
3
174
0
1
Order By: Relevance
“…Therefore, together with the observation that treatment with hypertonic sucrose (0.45 M) inhibited GPR109A internalization, we postulate that phosphorylated GPR109A binds arrestin3 after receptor activation, is targeted to clathrin-coated pits, and is then rapidly recycled back to the cell surface from perinuclear early endosomes after internalization (43,44). Walters et al (45) reported that niacin-induced stimulation of GPR109A led to arrestin-dependent signaling to ERK1/2 activation, and this pathway mediated the adverse side effect of cutaneous flushing but not the beneficial antilipolytic effect of niacin. Our results obtained from siRNA experiments demonstrated that knocking down GRK or arrestin expression in HEK-293 cells had no effect on ERK1/2 pathway activation.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, together with the observation that treatment with hypertonic sucrose (0.45 M) inhibited GPR109A internalization, we postulate that phosphorylated GPR109A binds arrestin3 after receptor activation, is targeted to clathrin-coated pits, and is then rapidly recycled back to the cell surface from perinuclear early endosomes after internalization (43,44). Walters et al (45) reported that niacin-induced stimulation of GPR109A led to arrestin-dependent signaling to ERK1/2 activation, and this pathway mediated the adverse side effect of cutaneous flushing but not the beneficial antilipolytic effect of niacin. Our results obtained from siRNA experiments demonstrated that knocking down GRK or arrestin expression in HEK-293 cells had no effect on ERK1/2 pathway activation.…”
Section: Discussionsupporting
confidence: 55%
“…MK-0354 has a beneficial nicotinic acid-like effect on serum lipids but, importantly, does not affect the ␤-arrestin pathway causing the side effect of flushing (17,55). For the ghrelin receptor, development of a biased agonist could have important therapeutic potential, as the receptor is responsible for both growth hormone secretion and induction of hunger and fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Niacin dose-dependently decreased platelet cyclic AMP, as expected, upon activation of this Gi-linked receptor (ref. 44 and Supplemental Figure 8E).…”
Section: Figurementioning
confidence: 95%